The relationship between doctrine of ultra vires & R Rama Chandran in the Malaysian and English administrative laws / Izmi Izdiharuddin Che Jamaludin Mahmud and Suria Fadhillah Md Pauzi - Che Jamaludin Mahmud, Izmi Izdiharuddin; Md Pauzi, Suria Fadhillah (Universiti Teknologi MARA, Pahang, 2022)
In the Malaysian administrative law, any person who aggrieves with the administrative decision is entitled to a judicial review to determine whether the administration fails to adhere to express or implied rules related to its establishment, i.e. ultra vires decision. The primary legal test for ultra vires decision for English and Malaysian administrative laws derives from the Wednesbury unreasonableness. Its jurisdiction further expands in the Council of Civil Service Unions v Minister for the Civil Service [1984] 3 All ER 935 ("GCHQ"), recognising another three categories of ultra vires decision, namely illegality, procedural impropriety and proportionality. Meanwhile, the Malaysian Court has also accepted the common law doctrine of legitimate expectation as part of a legal test in administrative law. Nevertheless, since R Rama Chandran v Industrial Court of Malaysia [1997] 1 MLJ 145 case ("R Rama Chandran"), the jurisdiction of judicial review in the Malaysian Court is further enlarged from subjective test to objective test, which allows the Court to examine the merit of the administrative decision and further engage in judicial activism. This article examines the relationship between the Wednesbury unreasonableness, GCHQ legal test, proportionality, legitimate expectation, and their relevance to the current Malaysian administrative law. This study is based on the doctrinal legal research method, and the outcome will ascertain applicable legal tests. The findings of this study would contribute to the body of knowledge in administrative law.